Hetero-structured nanomaterials for efficient photocatalytic conversion of carbon dioxide - Wang, Yan (Nanyang Technological University, 2023)
To harvest plentiful and enduring energy of the Sun, photocatalytic reduction of CO2 is one of the most promising strategies to diminish atmospheric CO2 concentration and generate valuable carbon fuels simultaneously. Among the candidates of potential photocatalysts, hierarchical hollow heterostructures have attracted significant research interest due to the intrinsic virtues, such as high abundance of active sites, shortened bulk-to-surface diffusion length of photoinduced carriers, promoted charge/mass transfer, and superior chemical and physical stability. This report focuses on the rational design and synthesis of hierarchical hollow structures for heterogenous photocatalysis. The main results and new findings in this work are summarized as follows. 1. NiCoOP NPs@MHCFs catalysts are designed and fabricated through confining nickel cobalt oxyphosphide nanoparticles (NiCoOP NPs) in multichannel hollow carbon fibers (MHCFs) for efficient CO2 photoreduction under solar light. Due to the ultrasmall size and high surface area, the mixed metal oxyphosphide NPs not only provide copious active sites for reactions but also shorten the diffusion length to promote the separation of photoinduced carriers, while the hollow carbon matrix can work as a “trap-well” for enhancing the light capture and CO2 absorption. The facile synthesis method permits tunable chemical compositions, and the optimized hetero metal oxyphosphide catalyst exhibits considerable activity for photosensitized CO2 reduction. 2. Hierarchical FeCoS2-CoS2 double-shelled nanotubes are developed via a facile two-step cation-exchange reactions for efficient photocatalytic CO2 reduction. The unique two-step synthesis strategy allows both shells of the double-shelled nanotubes assembled from ultrathin two-dimensional (2D) nanosheets, which can reduce the bulk-to-surface diffusion length to highly hinder the recombination of photogenerated electron-hole pairs. Meanwhile, the double-shelled nanotube structure offers large surface area to boost surface-dependent redox reactions and utilizes incident light more efficiently because of the multi-scattering of light in the cavity. As a result, these hierarchical FeCoS2-CoS2 double-shelled nanotubes exhibit superior activity and high stability for photosensitized deoxygenated CO2 reduction. 3. Metal–organic-framework-derived hierarchically ordered porous nitrogen and carbon co-doped ZnO (N-C-ZnO) structures are developed as nanoreactors with decorated CoOx nanoclusters for CO2-to-CO conversion driven by visible light. Despite suffering from slow charge-carrier mobility, photocatalysis is still an attractive and promising technology toward producing green fuels from solar energy. An effective approach is to design and fabricate advanced architectural materials as photocatalysts to enhance the performance of semiconductor-based photocatalytic systems. Introduction of hierarchical nanoarchitectures with highly ordered interconnected meso–macroporous channels shows beneficial properties for photocatalytic reduction reactions, including enhanced mobility of charge carriers throughout the highly accessible framework, maximized exposure of active sites, and inhibited recombination of photoinduced charge carriers. Density functional theory (DFT) calculations further reveal the key role of CoOx nanoclusters with high affinity to CO2 molecules, and the Co-O bonds formed on the surface of the composite exhibit stronger charge redistribution. As a result, the obtained CoOx/N-C-ZnO demonstrates enhanced photocatalysis performance in terms of high CO yield and long-term stability.